Pengaruh Kompensasi, Budaya Organisasi dan Motivasi terhadap Retensi Karyawan pada Store Maxx Coffee Tangerang - Jessica Angeline Nathania; Shierli Wijaya (Studi Ilmu Manajemen dan Organisasi, 2024)
Purpose: Coffee is an agricultural commodity product that is popular among the public because it has a unique taste and aroma, thus encouraging a high increase in demand for coffee. This encourages rapid development in coffee retail companies, and employees have become one of the factors in a company's success. Employees who feel cared for by the company and are satisfied with their work will make a significant contribution to the company in the form of increased performance, work achievement, and increased employee retention. The purpose of this research is to determine the influence of compensation, organizational culture, and work motivation on employee retention at the Maxx Coffee store. Research Methodology: The approach used in this study is a quantitative approach to data collection using research tools. The method applied in this study was a survey with a total research sample of 45 Maxx Coffee employees in Tangerang. Results: From the results of the research, it is known that compensation, organizational culture, and work motivation have partial effects on employee retention. But simultaneously it is known that compensation, organizational culture, and work motivation influence employee retention. Limitation: The limitation in this research is that because it uses a questionnaire, something that can happen is that sometimes the responses given can show a situation that is not true. The author focused only on regression models and quantitative research methods. Contribution: The author advises that Maxx Coffee can increase compensation and be able to adopt an organizational culture for all its employees, as well as motivate further improvement of Maxx Coffee's ability to retain its employees at the Tangerang branch.